(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research aims to identify the theoretical foundations for measuring and analyzing quality costs and continuous improvement, as well as measuring and analyzing quality costs for the Directorate of Electricity Supply / Middle Euphrates and continuous improvement of the distribution of electrical energy,The problem was represented by the high costs of failure and waste in electrical energy result to the excesses on the network and the missing (lost) energy,Thus, measuring and analyzing quality costs for the distribution of electrical energy and identifying continuous improvement leads to a reduction in missing and an increase in sales, as the research reached many conclusions, the most important of which is the high percentage of actual missing from electrical energy compared to the percentage of permissible missing which led to high costs of external failure as it reached Searching to many recommendations, the most important of which is the need to intensify the procedures of distribution directorates regarding lifting excesses and taking legal deterrent against violators on the electrical network.